2017
DOI: 10.1016/j.neubiorev.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effects of intranasal oxytocin on interpretation and expression of emotions

Abstract: Highlights-Single dose of intranasal oxytocin has little to no effect on emotional theory of mind or emotion expression among healthy or clinical adult populations -Intranasal oxytocin improved recognition of basic emotions, particularly fear, but only among healthy populations -Intranasal oxytocin improves sensitivity to recognise anger, but only among healthy populations -Effect of oxytocin may be dependent on social boundaries 1 Abstract Accurate interpretation and appropriate expression of emotions are key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 83 publications
8
103
2
4
Order By: Relevance
“…Additionally, the fact that IN-OT influences explicit and implicit measures of the malleability of body representation is in line with previous findings showing that oxytocin sharpens the recognition of basic emotions as well as hidden/implicit emotional facial expressions (Leknes et al, 2013;Leppanen et al, 2017 for a meta-analysis). This explanation supports the idea that oxytocin might play an important evolutionary role, by promoting social affiliation and bonding and by downregulating pain perception associated with reproduction (Insel, 1992;Paloyelis et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the fact that IN-OT influences explicit and implicit measures of the malleability of body representation is in line with previous findings showing that oxytocin sharpens the recognition of basic emotions as well as hidden/implicit emotional facial expressions (Leknes et al, 2013;Leppanen et al, 2017 for a meta-analysis). This explanation supports the idea that oxytocin might play an important evolutionary role, by promoting social affiliation and bonding and by downregulating pain perception associated with reproduction (Insel, 1992;Paloyelis et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…In total, the search process yielded 80 unique studies. Based on the titles and abstracts, 68 studies were rejected . Based on full text review of the remaining 12 studies, five were rejected for being short‐term studies (less than a month), while one was rejected for not being a randomized controlled trial .…”
Section: Resultsmentioning
confidence: 99%
“…Our data linking low serum oxytocin levels to higher alexithymia scores in women with AN are consistent with these findings and support the hypothesis that low oxytocin might contribute to these symptoms. A study investigating the impact of single‐dose intranasal oxytocin (40 IU) did not find evidence for an improvement of social‐emotional functioning in AN (Leppanen, Cardi, et al, ), and a recent meta‐analysis showed improvements of social‐emotional functioning following intranasal oxytocin administration in healthy individuals but not in clinical populations (Leppanen, Ng, Tchanturia, & Treasure, ). However, it is important to note that these studies used supraphysiologic levels of oxytocin, while our study investigated the link between physiologic levels of oxytocin and social‐emotional functioning.…”
Section: Discussionmentioning
confidence: 99%